Endoscopic radiofrequency ablation for early esophageal squamous cell neoplasia: report of safety and effectiveness from a large prospective trial - He, Shun; Bergman, Jacques; Zhang, Yueming; Weusten, Bas; Xue, Liyan; Qin, Xiumin; Dou, Lizhou; Liu, Yong; Fleischer, David; Lu, Ning; Dawsey, Sanford M.; Wang, Gui-Qi (Endoscopy, 2015)
Background and study aims: Endoscopic radiofrequency ablation (RFA) is an established therapy for Barrett’s esophagus. Preliminary reports, limited by low patient numbers, also suggest a possible role for RFA in early esophageal squamous cell neoplasia (ESCN). The aim of this study was to evaluate the safety and effectiveness of RFA for early ESCN (moderate/high grade intraepithelial neoplasia [MGIN/HGIN] and early flat-type esophageal squamous cell carcinoma [ESCC]).Patients and methods: This prospective cohort study included patients with at least one flat (type 0-IIb) unstained lesion (USL) on Lugol’s chromoendoscopy and a consensus diagnosis of MGIN, HGIN, or early ESCC. RFA was used at baseline to treat all USLs, and then biopsy (and focal RFA if USL persisted) was performed every 3 months until all biopsies were negative for MGIN, HGIN, and ESCC. The main outcome measurements were complete response at 3 and 12 months (absence of MGIN, HGIN, and ESCC), neoplastic progression, and adverse events.Results: A total of 96 patients participated (MGIN 45, HGIN 42, early ESCC 9). At 3 and 12 months, 73 % (70/96) and 84 % (81/96), respectively, showed a complete response. Two patients (2 %) progressed (MGIN to HGIN; HGIN to T1m2 ESCC); both were treated endoscopically and achieved complete response. Stricture occurred in 20 patients (21 %), all after circumferential RFA. Lugol’s + RFA 12 J/cm2 (single application, no cleaning) was the favored baseline circumferential RFA technique (82 % 12-month complete response [14/17], 6 % stricture [6/17]). Conclusion: In patients with early ESCN, RFA was associated with a high complete response rate and an acceptable safety profile.